The influence of mineral fertilizer application and plant nutrition on plantparasitic nematodes in upland and lowland rice in Cote dIvoire and its implications in longterm experiments - Coyne, D.; Sahrawat, K.; Plowright, R. (Cambridge University Press, 2004)
Mineral fertilizer application and consequent plant nutrition has long been observed to influence associated plant-parasitic nematode population densities, offering the potential as a nematode management option. Observations were made on the influence of mineral fertilizer application on nematode populations on three separate long-term rice experiments, (differential mineral application on upland and on lowland rice, and P application on upland rice) undertaken between 1994 and 1997 in Côte d'Ivoire. In 1995, on upland rice, treatments with K or N withheld from the comprehensive mineral application treatment (range of elements including N, P, K, Ca, Mg and Zn) led to lower densities of Pratylenchus zeae at harvest than the comprehensive mineral application. By withholding K or Mg, Helicotylenchus pseudorobustus densities were greater than with either the control (no mineral application) or comprehensive mineral application in the same year. No differences were observed between treatments in 1994, or between treatments for densities of other nematode species present (Meloidogyne incognita, Criconemella tescorum) or for total nematode density. In the lowland rice trial, no treatment effects on nematode species (Hirschmanniella oryzae and Uliginotylenchus palustris) were observed. In the P application trial on a P-deficient Ultisol, Heterodera sacchari densities were lower in treatments receiving 180 kg P ha−1, than untreated in 1995; in 1996 no differences were observed between untreated and 135 kg P ha−1, while in 1997 higher densities of H. sacchari were present in 135 kg P ha−1 than untreated. Regression analysis of nematode densities against the mineral straw content in the P application trial revealed a negative correlation between M. incognita and Mn and Ca, and between P. zeae and Zn or Fe. A positive correlation was observed between Helicotylenchus spp. and Mg. This study provides strong arguments for taking plant parasitic nematodes into account when planning and executing long-term research trials.